2017
DOI: 10.1111/add.13886
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cannabis potency and prices in a newly legal market: evidence from 30 million cannabis sales in Washington state

Abstract: Aims To (1) assess trends and variation in the market share of product types and potency sold in a legal cannabis retail market, and (2) estimate how potency and purchase quantity influence price variation for cannabis flower. Design Secondary analysis of publicly available data from Washington State’s cannabis traceability system spanning July 7, 2014 to September 30, 2016. Descriptive statistics and linear regressions assessed variation and trends in cannabis product variety and potency. Hedonic regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
228
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(239 citation statements)
references
References 58 publications
7
228
2
2
Order By: Relevance
“…These data were collected in a single geographical region, and improved global monitoring of cannabis potency and health-related outcomes may be necessary to investigate these associations elsewhere (Freeman & Swift, 2016). However, our findings highlight a cause for concern regarding the health impact of extremely potent cannabis concentrates (∼70% THC) which have very recently risen in popularity in some parts of the USA (Smart et al 2017). In a rapidly changing cannabis climate, it is essential that policy makers consider the effects of new legislation on cannabis potency and the incidence of cannabis-related harms.…”
Section: Discussionmentioning
confidence: 86%
“…These data were collected in a single geographical region, and improved global monitoring of cannabis potency and health-related outcomes may be necessary to investigate these associations elsewhere (Freeman & Swift, 2016). However, our findings highlight a cause for concern regarding the health impact of extremely potent cannabis concentrates (∼70% THC) which have very recently risen in popularity in some parts of the USA (Smart et al 2017). In a rapidly changing cannabis climate, it is essential that policy makers consider the effects of new legislation on cannabis potency and the incidence of cannabis-related harms.…”
Section: Discussionmentioning
confidence: 86%
“…While CBD is believed to be neuroprotective, THC has been found to exacerbate alterations in brain regions such as the prefrontal cortex and hippocampus, and higher doses of marijuana use are particularly associated with such alterations (Lorenzetti et al, 2016). In states with legal marijuana markets (such as Washington), average THC levels for cannabis extracts have been found to be more than three times those for cannabis flowers (Smart et al, 2017). Frequent use of high-potency marijuana has been associated with dependence severity (Freeman and Winstock, 2015), and increases in potency have been linked with increases in first-time admissions to drug treatment for problems associated with cannabis (Freeman et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A study from the Netherlands found that THC concentrations in cannabis products sold at retail outlets from 2000 to 2015 had roughly doubled from 2000 to 2015 [11]. New products on the market are even higher in THC: cannabis extracts (used for “dabbing”) have more than triple the THC content of the buds or other plant parts commonly used for smoking (68.7 vs. 20.6%) [12]. However, it is hard to discuss cannabinoids as if they were one single substance; even among botanical marijuana offerings, there are numerous varieties and diverse methods of consumption (smoking, “vaping,” edibles).…”
Section: Resultsmentioning
confidence: 99%